Widows in India - Thara Bhai, L. (Delhi : B.R. Pub. Corp., 2004)
On the social and economic conditions of widows of Tamil Nadu, India; a study.
Includes statistical tables.
Keywords: Widows -- India -- Tamil Nadu -- Social conditions; Widows -- India -- Tamil Nadu -- Social conditions -- Statistics; Widows -- India -- Tamil Nadu -- Economic conditions